DEVELOPMENT OF CALCULATION METHODS OF TORSIONAL STIFFNESS IN FLEXIBLE DISC COUPLING - FERNANDO (NIM : 13106065); Pembimbing: Prof. Dr. Indra Nurhadi , DEDY
The existence of the reciprocating engines like a diesel engine as a driver unit or reciprocating compressor as a driven unit in a mechanical system has lead to torque fluctuation. Torque fluctuation can cause the occurrence of torsional vibration problems on the system. Torsional vibration is a serious problem on the reciprocating engine with its system because it can cause failure of the crankshaft, gears, shafts, coupling and others. The problem occurs when the natural frequency of torsional vibration are excited by the fluctuations of torque equal to natural frequency component or system. In order for such diesel engine system has high reliability, then the torsional vibration analysis needs to be done. In this final project, the procedure for calculating the important parameters required in the analysis of torsional vibration, namely torsional stiffness of flexible couplings is described. Geometrical modeling for solid components was carried out by using Autodesk Inventor 2010, while thin components such as flexible membrane was modeled directly using Ansys Workbench 11. For finite element analysis, software Ansys Workbench 11 was used. A case study using a disc coupling manufactured by John Crane TLC Metastream T Series Coupling was carried out. For a such particular coupling, it was found that the value of stiffness is 1,894 x 106 N.m/rad and the moment of inertia is 97.180,6367 kg.mmÃ‚Â².